2018
DOI: 10.1186/s13063-018-2615-6
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences for mother and baby of substantial pre-conception weight loss in obese women: study protocol for a randomized controlled trial

Abstract: BackgroundCurrent guidelines for the management of obesity in women planning pregnancy suggest lifestyle modification before conception. However, there is little evidence that lifestyle modification alters pregnancy outcomes. Bariatric surgery results in significant weight loss. This appears to reduce the risk of adverse pregnancy outcomes for the mother but may increase the risk of adverse outcomes for the infant. In order to reduce the risks of obesity-related adverse pregnancy outcomes for both mother and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 65 publications
0
16
1
12
Order By: Relevance
“…On the other hand, regarding maternal body mass index at delivery the prevalence of maternal overweight and obesity is increasing and has important consequences for the health of mother and child at delivery (Price et al, 2018). In the present study percentage of obese women in control group was about one third of the mind it was significantly greater than in intervention group.…”
Section: Discussioncontrasting
confidence: 43%
“…On the other hand, regarding maternal body mass index at delivery the prevalence of maternal overweight and obesity is increasing and has important consequences for the health of mother and child at delivery (Price et al, 2018). In the present study percentage of obese women in control group was about one third of the mind it was significantly greater than in intervention group.…”
Section: Discussioncontrasting
confidence: 43%
“…However, to date, not a single randomized controlled trial has demonstrated effective means of weight loss, which lead to improved pregnancy outcomes for both mother and baby. An ZCTR study is currently registered in Australia, which aims to determine the best approach to weight loss during pregnancy planning [32] The study will include 164 patients with a BMI of 30 -55 kg/m 2 . Patients will be divided into two groups: the first-patients in whom a slight decrease in body weight by 3% -5% s is planned using a moderately hypocaloric diet for 12 months, the second-patients who are planning a significant reduction in body weight by 10% -15% using a modified pronounced low-energy diet [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have demonstrated that perturbations of the maternal physiology during the peri-conceptional period (e.g., maternal diet) have impact both on preimplantation phenotype and long-term development and could lead to impaired health during adulthood [26]. Emerging evidence suggests the metabolic status of the mother may "program" the offspring's long-term risk of metabolic disease [27].…”
Section: Maternal Health At Preconception Periodmentioning
confidence: 99%